2019
DOI: 10.1302/0301-620x.101b6.bjj-2018-1488.r1
|View full text |Cite
|
Sign up to set email alerts
|

Increased conditional risk of recurring complications with contralateral total hip arthroplasty surgery

Abstract: Aims Increasingly, patients with bilateral hip arthritis wish to undergo staged total hip arthroplasty (THA). With the rise in demand for arthroplasty, perioperative risk assessment and counselling is crucial for shared decision making. However, it is unknown if complications that occur after a unilateral hip arthroplasty predict complications following surgery of the contralateral hip. Patients and Methods We used nationwide linked discharge data from the Healthcare Cost and Utilization Project between 2005 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
7
1
Order By: Relevance
“…A larger proportion of cases (29.0%) in the INR≤0.9 group had contralateral THA than other groups with statistical signi cance. Some other studies showed contralateral surgery increases the risk of recurring complications in both THA and TKA [24,25]. We did not nd this trend in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…A larger proportion of cases (29.0%) in the INR≤0.9 group had contralateral THA than other groups with statistical signi cance. Some other studies showed contralateral surgery increases the risk of recurring complications in both THA and TKA [24,25]. We did not nd this trend in our study.…”
Section: Discussioncontrasting
confidence: 75%
“…Even though the origin of these complications is not completely clear, they can be due to exacerbated immune responses of the body against foreign body material 16 . Problems with long term safety and reversibility of adverse events due to foreign body material also occur in plastic surgery (breast implants), 11 cardiology (pacemakers), 12 and orthopedics (hip implants) 13 . When looking at the genetic predisposition leading to immune‐mediated, adverse reactions, and genes within the major histocompatibility complex (MHC) have been shown to be associated with auto‐immune diseases as M. Bechterew 17 .…”
Section: Introductionmentioning
confidence: 99%
“…16 Problems with long term safety and reversibility of adverse events due to foreign body material also occur in plastic surgery (breast implants), 11 cardiology (pacemakers), 12 and orthopedics (hip implants). 13 When looking at the genetic predisposition leading to immune-mediated, adverse reactions, and genes within the major histocompatibility complex (MHC) have been shown to be associated with auto-immune diseases as M. Bechterew. 17 And there is also speculation about the HLA subtype-B*08 and HLA subtype-DRB1*03 in immune mediated disorders in women with silicone breast implants.…”
mentioning
confidence: 99%
“…4–7 This has been reported with other foreign materials 8,9 such as breast implants, 10 pacemakers, 11 and prosthetic joints. 12…”
mentioning
confidence: 99%